Making the "Citizen Constitution": Popular Participation in the Brazilian Transition to Democracy, 1985–1988. Issue 4 (October 2022) - McDonald, Daniel
Abstract: This article examines popular participation in the making of Brazil's 1988 post-authoritarian "Citizen Constitution." In 1987, Brazilians submitted 122 popular amendments ( emendas populares ) supported by over 12 million signatures to the National Constituent Assembly (1987–88). As this article contends, this extraordinary experiment in popular constitution-making problematizes notions of Brazil's transition from authoritarian to democratic rule as the most conservative of those that swept Latin America at the end of the Cold War. The popular amendments emerged amid a nationwide campaign for popular participation that saw millions of Brazilians participate in letter-writing campaigns, protests, and debates over the constitution that carried over into the halls of the Constituent Assembly itself. I argue that the popular amendments countered the arbitrary authoritarianism of the Brazilian civil-military dictatorship (1964–85) with a constitutionalism in which everyday Brazilians would safeguard democracy through popular participation in government. While only partially consolidated, this vision offered diverse marginalized groups an opportunity to claim full citizenship in Brazil's nascent democracy, especially in ways that more overtly addressed issues of race, ethnicity, gender, and disability. This article thus shows that far from being the exclusive province of political elites, everyday people meaningfully shaped the constitutional restorations in late twentieth-century Latin America.